The Competitive Advantage of CCC in Integrated Services of Construction in Indonesia - Li Wenjiang; Jacob Tan (Milestone: Journal of Strategic Management, 2025)
In the background of global infrastructure construction and the transformation of the construction industry to an integrated service model, this study draws on strategic management theory, especially Porter's theory of competitive advantage and the resource-based view (RBV), to explore the research questions: 1. What are the strategic factors that contribute to the competitive advantage of CCC? 2. How are the strategic factors applied/implemented to contribute to the competitive advantage of CCC. And draw the competitive advantages of CCC to maintain its leading position in the highly competitive integrated building services field. This study is mainly based on interviews, through qualitative research and literature analysis, to explore the factors that CCC uses to build differentiated competitive advantages. The development of CCC in Indonesia shows that Chinese enterprises should pay attention to the comprehensive balance of technical capabilities, quality control, social responsibility and employee development in the process of "going out" to achieve a high-quality and responsible international development path. The researchers hope that this study can provide some reference for peer companies to enhance their competitive advantages, and at the same time provide strategic inspiration for international customers and other researchers to understand how Chinese integrated building service providers can gain competitive advantages in the evolving global infrastructure ecosystem.